Adults with ADD or ADHD and Their Perceptions of Distance Learning: A Plan for Future Research - Brandi Petz (Adult Education Research Conference, 2010)
Attention Deficit Disorder and Attention Deficit Hyperactivity Disorder are becoming more commonly recognized in adults, though it used to be held as an adolescent issue. Many people still believe these disorders only affect young people, but “experts estimate that as many as one third of adolescents who have been diagnosed with ADHD will carry the disorder with them into adulthood.” (ADHD Among College Students, n.d.) Some symptoms of ADD and ADHD are: difficulty paying attention, difficulty concentrating, extreme levels of activity, and being very easily distracted. These disorders in adults affect relationships and can cause problems at work and in school. College students with ADHD appear to be at higher than average risk for academic underachievement relative to their non-ADHD counterparts. (College Students with ADHD, n.d.)